2018
DOI: 10.1021/acscatal.8b02311
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Electrohydrogenation of N2 to NH3 Catalyzed by Multishelled Hollow Cr2O3 Microspheres under Ambient Conditions

Abstract: Electrohydrogenation of N2 to NH3 is emerging as an environmentally benign strategy to tackle the issues associated with the energy-intensive, CO2-emitting Haber–Bosch process. However, the method is severely challenged by N2 activation and needs efficient N2 reduction reaction (NRR) catalysts. Here, we report that multishelled hollow Cr2O3 microspheres (MHCMs), which are synthesized by a facile synthetic route, can serve as efficient and selective non-noble metal electrocatalysts for NRR. In 0.1 M Na2SO4 solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
145
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 274 publications
(148 citation statements)
references
References 53 publications
3
145
0
Order By: Relevance
“…Both NH 3 yields and FEs initially increase with potential being more negative. , 6.78%), [51] and TiO 2 -rGO (15.13 µg h −1 mg −1 cat. These results might result from the competitive hydrogen-evolving process, which can be suppressed in nonaqueous media to achieve higher current efficiency.…”
mentioning
confidence: 99%
“…Both NH 3 yields and FEs initially increase with potential being more negative. , 6.78%), [51] and TiO 2 -rGO (15.13 µg h −1 mg −1 cat. These results might result from the competitive hydrogen-evolving process, which can be suppressed in nonaqueous media to achieve higher current efficiency.…”
mentioning
confidence: 99%
“…Finally, the difference in the physicochemical properties of different surfaces should also be taken into consideration. For example, it has been reported that the internal surfaces may be less capped relative to external surfaces in multi‐shelled hollow Cr 2 O 3 microspheres, implying that the internal surfaces are catalytically more active (Figure d) . Overall, pore structure control was demonstrated to be effective for enhancing NRR, although further research in this field is warranted.…”
Section: Design Principles For Electrocatalystsmentioning
confidence: 94%
“…d) Multishell hollow Cr 2 O 3 microspheres as NRR catalysts. Adapted with permission . Copyright 2018, American Chemical Society.…”
Section: Design Principles For Electrocatalystsmentioning
confidence: 99%
“…Previous studies have proved that noble‐metal based catalysts are efficient N 2 reduction reaction (NRR) electrocatalysts, but their large‐scale uses are severely limited by the high cost and rareness. Considerable recent attention has thus focused on earth‐abundant transition metal‐based alternatives to effectively catalyze the NRR . Nevertheless, metal ions may be released from such catalysts, leading to environmental pollution.…”
Section: Figurementioning
confidence: 99%